PERTANGGUNGJAWABAN PIDANA DOKTER YANG MELAKUKAN PELANGGARAN KERAHASIAAN REKAM MEDIS PASIEN BERDASARKAN UNDANG-UNDANG NOMOR 29 TAHUN 2004 TENTANG PRAKTIK KEDOKTERAN - RIA RATNA SARI BR. NAINGGOLAN; Dessy Artina; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The obligation to keep medical secrets often gets less attention from doctors. It is strongly suspected that there are still doctors disclosing the patient's secrets so that the patient's rights feel neglected and the patient's honor is not maintained anymore. The purpose of this thesis, namely; First, the criminal responsibility of the doctor who violates the confidentiality of the medical record if he is unable to obtain the patient's permission; second, the settlement of a criminal case of a doctor who violates the confidentiality of a patient's medical record. This type of research is normative legal research, which is a study of legal principles that examines legal norms on legal rules, namely the law. This research is descriptive, which is a study that aims to make a picture of the problem. From the results of the research and discussion it can be concluded that first: a doctor in the accountability of criminal acts of confidential leakage violations of medical records can be resolved through 2 (two) ways, namely litigation (court) and non litigation. To resolve violations of medical records, complete the legal channels that have been regulated based on the applicable law; secondly, in the settlement of litigation path cases (court) criminal cases open the medical record the same process which distinguishes only the presence of an expert witness in the medical field to help the judge to decide the case. Suggestion by the author, first: medical records as patient rights that must be maintained and a doctor has the right to respect and not ignore what constitutes the confidentiality of the patient's illness and in carrying out his duties doctors must uphold the values of medical ethics. Second: the union of criminal sanctions opening the secrets of medicine leaking medical records that are more assertive and still maintaining the interests of patients does not ignore the rights of patients who should be protected, even though it is a minor violation still need to maintain the honor of the patient and not ignore the doctor's profession.